Philosophy of economics: the analysis of alternative directions - Gerashchenko Igor Germanovich (Studia Humanitatis)
Alternative directions in modern economic theory assume philosophical justification. The paper provides methodological analysis of the following alternative directions in economics: the new Austrian school, modern institutionalism, radical political economy, post-Keynesian economics, natural-scientific economic theory, traditionalist economics, agricultural economics, feminist economic theory. The author substantiates the idea that heterodox economic theory poses such problems that cannot find an adequate solution within the framework of economics. Therefore, there is an urgent need to create a new economic theory that would synthesize orthodox and unorthodox doctrines.